2014
DOI: 10.1039/c3nr04540d
|View full text |Cite
|
Sign up to set email alerts
|

Supporting palladium metal on gold nanoparticles improves its catalysis for nitrite reduction

Abstract: Nitrate (NO3(-)) and nitrite (NO2(-)) anions are often found in groundwater and surface water as contaminants globally, especially in agricultural areas due to nitrate-rich fertilizer use. One popular approach to studying the removal of nitrite/nitrate from water has been their degradation to dinitrogen via Pd-based reduction catalysis. However, little progress has been made towards understanding how the catalyst structure can improve activity. Focusing on the catalytic reduction of nitrite in this study, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 43 publications
5
52
0
Order By: Relevance
“…It was not known how the oxidation states of Pd-on-Au would be affected by the harsher conditions of glycerol oxidation (60 C, O 2 atmosphere, and pH $ 13.5) compared to those of TCE HDC (room temperature, H 2 atmosphere, near-neutral pH). [36][37][38][39][40][41][42] We thus performed ex situ XANES characterization on 4 samples (Au NPs, Pd NPs, and the two Pd-on-Au NP compositions) under 3 conditions: as-prepared, before the oxidation reaction, and aer the oxidation reaction.…”
Section: Assessment Of Reaction Environment On Metal Oxidation State mentioning
confidence: 99%
“…It was not known how the oxidation states of Pd-on-Au would be affected by the harsher conditions of glycerol oxidation (60 C, O 2 atmosphere, and pH $ 13.5) compared to those of TCE HDC (room temperature, H 2 atmosphere, near-neutral pH). [36][37][38][39][40][41][42] We thus performed ex situ XANES characterization on 4 samples (Au NPs, Pd NPs, and the two Pd-on-Au NP compositions) under 3 conditions: as-prepared, before the oxidation reaction, and aer the oxidation reaction.…”
Section: Assessment Of Reaction Environment On Metal Oxidation State mentioning
confidence: 99%
“…However, the concentration of nitrite ions in the RO permeate remained higher than the regulated level (1.0 mg N/L or 4.9 mg NaNO À 2 /L) [24] set by the United States Environmental Protection Agency (US EPA). Therefore, IX was used to further remove nitrite.…”
Section: Treatment Of the Ro Permeatementioning
confidence: 91%
“…The Hörold group reported that the ammonium formation was favored in the high pH conditions [2]. In order to lower pH values, Qian et al used CO 2 gas as a pH buffer for the nitrite reduction [46]. Accordingly, we tested the PCZ1 catalyst (which had the best activity) under constant H 2 flow rate of 90 mL/min and varied CO 2 of 10, 30, 60 and 90 mL/min.…”
Section: Reaction Testsmentioning
confidence: 98%